Using advanced simulation techniques to improve industrial controller’s dependability - Seabra, Eurico (2011)
Modelica Modeling language is powerful and suitable for modeling mechatronic systems, being possible to interact different technological aspects and deal, simultaneously with different technologies (mechanical, electrical, pneumatic, hydraulic,..). In this paper it is discussed, in a case study, the possibility of using this language for modeling an automation system (controller and plant) in closed loop behavior and also in defining some parameters of the automation system in order to optimize some behavior aspects of the system as, for instance, the time cycle of the automation system. Some aspects relied with controllers dependability are also discussed and it is showed how Modelica modeling language can help controllers’ designers improving controllers dependability, when are used Simulation Techniques.